Genetic Variability, Heritability and Correlation of Quantitative Traits in Fine and Aromatic Rice Landraces of Nepal - Tiwari, Dev Nidhi; Pandey, Madhav Prasad; Manandhar, Hira Kaji; Bhusal, Tej Narayan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Landraces are reservoirs of desirable and important traits and sources of variations for crop improvement. We evaluated 150 fine and aromatic rice landraces obtained from various regions of the country. The study employed alpha lattice design with two repetitions. Genetic parameters and association studies were performed on the fourteen quantitative traits. Statistical analysis of quantitative traits from evaluated rice landraces revealed significant (p< 0.05) differences for all the traits except the number of unfilled grains. Heading (18.08 and 18.29), maturity days (13.76 and 13.92), and thousand grain weight (20.26 and 21.74) showed narrow variation in genotypic and phenotypic coefficients. Similarly, heading (0.98 and 36.83), maturity days (0.98 and 28.03), plant height (0.72 and 27.66), and thousand grain weight (0.87 and 38.88) recorded high heritability coupled with high genetic advance as percentage of mean. Flag leaf length (0.34**), width (0.31**), and thousand grain weight (0.39**) had highly significant correlation with grain yield. Besides, days to heading (-0.57**, -0.38**) and maturity (-0.57**, -0.38**), tillers (-0.40**, -0.21) were highly significant but negatively correlated. Balamsari Dhan produced the highest grain yield (6.2 t/ha) followed by Rango (5.35 t/ha). The outstanding genotypes could be utilized as donor parents in the future breeding to enhance genetic gain.